Significantly Elevated Uterine Artery Doppler Indices and Impaired Subendometrial Perfusion Characterise Infertile Women in a North-Eastern Nigerian Population: A Case-Control Study - Mohammed Lawan Mohammed; Zara Baba Shettima; Maryam Abba Goni; Ibrahim Abba Tijjani; Umar Hassan Umar; Abubakar Farate; Zara Mohammed Bata; Abubakar Garba Farouk (West African Journal of Allied Health Sciences, 2026)
Background: Objectives: This study aims to determine and compare uterine artery Doppler indices and subendometrial blood flow patterns between infertile and fertile parous women in Maiduguri, Nigeria, a region within Africa's high-prevalence infertility belt. Methods: This prospective case-control study was conducted over 13 months period involving 300 newly diagnosed cases of infertile women and 300 aged-matched fertile parous controls. Transvaginal Doppler ultrasound was performed during the mid-luteal phase. Uterine artery pulsatility index (PI) and resistivity index (RI) were measured, and subendometrial blood flow was classified into zones (1-4). Main Outcome Measures mean uterine artery Pulsatility Index, Resistivity Index, and distribution of subendometrial blood flow zones. Results: The mean age was 30.3±7.0 years for cases and 34.7±6.9 years for controls (p